Resources and competitiveness in Mexico’s industrial food and beverage sub-branches (2004, 2009 y 2014) (National Administration Journal, 2019)
The research work includes a quantitative analysis of there resources available for the food and beverages industrial sub-branches  to generate  sales  and diminish competition in their respective competitive environments in Mexico for the 2004, 2009 and 2014 periods according to the economic census in INEGI. The evidence shows that initial inventories balances are a valuable resource because it positively affects sales and erodes competition, thus denoting the necessary elements to be a sustainable or superior competitive advantage.
Keywords: Competitive Advantage; Inventories; Sales; Entry Barriers; Strategies